2017
DOI: 10.1080/03630269.2017.1340305
|View full text |Cite
|
Sign up to set email alerts
|

Coinheritance of Hb Bristol-Alesha [β67(E11)Val→Met;HBB: c.202G>A] and the α212 Patchwork Allele in a Brazilian Child with Severe Congenital Hemolytic Anemia

Abstract: Hb Bristol-Alesha [HBB: c.202G>A; β 67 Val>Met] is a rare structural variant of hemoglobin (Hb) resulting from a GTG>ATG substitution at codon 67 of the β-globin gene that leads to the replacement of valine by methionine in the corresponding position of the β-globin chain. The methionine residue is subsequently modified to aspartic acid [β67(E11)Val-Met→Asp], possibly by autoxidation mechanisms. This substitution prevents normal non-polar binding of Val67 to the heme group, resulting in molecular instability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…According to this study and the previous analysis [ 1 - 3 , 6 , 7 , 8 ] that were carried out on the Hb Alesha-Bristol, it has been confirmed that this mutation is always caused as a result of a de novo mutation. It has also been reported in subjects of different origins, three from Japan, two from Russia, as well as one from each of German, Argentina, Brazil, China, and Britain, suggesting that this mutation is not dependent on especial origins [ 7 , 9 ] . Moreover, the similar mutation has been reported in α-globin chain (α62(E11) Val to Met, i.e.…”
Section: Discussionsupporting
confidence: 73%
“…According to this study and the previous analysis [ 1 - 3 , 6 , 7 , 8 ] that were carried out on the Hb Alesha-Bristol, it has been confirmed that this mutation is always caused as a result of a de novo mutation. It has also been reported in subjects of different origins, three from Japan, two from Russia, as well as one from each of German, Argentina, Brazil, China, and Britain, suggesting that this mutation is not dependent on especial origins [ 7 , 9 ] . Moreover, the similar mutation has been reported in α-globin chain (α62(E11) Val to Met, i.e.…”
Section: Discussionsupporting
confidence: 73%
“…The Met residue is subsequently modified to Asp, probably via oxidative mechanisms (10). To the best of our knowledge, only 15 cases of this variant have been reported, all of which were dependent on blood transfusion (Table 1) (8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). According to this case and a previous analysis conducted on Hb Bristol-Alesha, it is always caused by de novo mutations.…”
Section: Discussionmentioning
confidence: 72%